Round Goby-Induced Changes in Young-of-Year Yellow Perch Diet and Habitat Selection - (:unkn) unknown (My University, 2015)
A critical step in the recruitment of age-0 yellow perch (Perca flavescens) to the adult population occurs during their transition to the demersal stage. If larval age-0 yellow perch survive recruitment bottlenecks imposed by alewife (Alosa pseudoharengus) and dreissenid mussels, they transition to demersal feeding in late August and early September. In Lake Michigan, demersal age-0 yellow perch seek rock substrate where they begin feeding on benthic invertebrates in late summer. That research preceded the invasion of the round goby (Neogobius melanostomus), a species that can have negative impacts on benthic forage. The current study used the spread of round gobies as a natural experiment to assess the competitive interactions between age-0 yellow perch and round gobies. Habitat selection and diet of age-0 yellow perch in relation to round goby abundance were analyzed using fish captured in 6.25- and 8-mm bar micro-mesh gill nets in 2006 and 2007 at six study locations from Sheboygan to Wind Point, Wisconsin. Age-0 yellow perch in this study significantly shifted habitat (from rock to sand) and diet preferences (from benthic invertebrates to zooplankton) with increasing round goby abundance. Round gobies also significantly altered the benthic community composition. I propose demersal age-0 yellow perch in Lake Michigan face a novel recruitment bottleneck caused by a combination of exploitative competition for benthic prey and interference competition with round gobies.
Keywords: Competition; Lake Michigan; Round Goby; Yellow Perch